2017
DOI: 10.1021/jacs.7b06555
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Controlled Epigenome Editing through an Inducible dCas9 System

Abstract: Although histone modifications are associated with gene activities, studies of their causal relationships have been difficult. For this purpose, we developed an inducible system integrating dCas9-based targeting and chemically induced proximity technologies to allow small molecule induced recruitment of P300 acetyltransferase and the acetylation of H3K27 at precise gene loci in cells. Employing the new technique, we elucidated the temporal order of histone acetylation and gene activation, as well as the stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 29 publications
0
47
0
Order By: Relevance
“…The CiA system described above utilized a knock-in DNA sequence at the OCT4 locus to enable the recruitment of epigenome modifiers through corresponding DBDs, which limits the inducible epigenome editing or remodeling to occur only at this particular locus. To offer a more versatile temporal-controlled epigenome editing platform, CRISPR/dCas9 was combined with the ABA-based CIP method to temporally target the ABI-fused p300 HAT core domain via PYL-fused dCas9 to the promoter region of IL1RN, MYOD1, GRM2 and HBA genes in human HEK293T cells leading to increased H3K27ac and gene activation (Figure 2b) [86]. With the fast dimerization kinetics that ABA CIP offers, the p300 HAT recruitment, H3K27ac installation and mRNA expression can be monitored following its precise time course, allowing the establishment of their causal relationship [86].…”
Section: Chemically Induced Proximity (Cip)-based Editingmentioning
confidence: 99%
See 1 more Smart Citation
“…The CiA system described above utilized a knock-in DNA sequence at the OCT4 locus to enable the recruitment of epigenome modifiers through corresponding DBDs, which limits the inducible epigenome editing or remodeling to occur only at this particular locus. To offer a more versatile temporal-controlled epigenome editing platform, CRISPR/dCas9 was combined with the ABA-based CIP method to temporally target the ABI-fused p300 HAT core domain via PYL-fused dCas9 to the promoter region of IL1RN, MYOD1, GRM2 and HBA genes in human HEK293T cells leading to increased H3K27ac and gene activation (Figure 2b) [86]. With the fast dimerization kinetics that ABA CIP offers, the p300 HAT recruitment, H3K27ac installation and mRNA expression can be monitored following its precise time course, allowing the establishment of their causal relationship [86].…”
Section: Chemically Induced Proximity (Cip)-based Editingmentioning
confidence: 99%
“…To offer a more versatile temporal-controlled epigenome editing platform, CRISPR/dCas9 was combined with the ABA-based CIP method to temporally target the ABI-fused p300 HAT core domain via PYL-fused dCas9 to the promoter region of IL1RN, MYOD1, GRM2 and HBA genes in human HEK293T cells leading to increased H3K27ac and gene activation (Figure 2b) [86]. With the fast dimerization kinetics that ABA CIP offers, the p300 HAT recruitment, H3K27ac installation and mRNA expression can be monitored following its precise time course, allowing the establishment of their causal relationship [86]. Furthermore, the reversibility of the ABA CIP system allowed the rapid removal of inducer and the dislodge of P300 HAT from the targeted locus, offering an opportunity to assess the stability of artificially installed H3K27ac and a model to study epigenetic memory [87,88].…”
Section: Chemically Induced Proximity (Cip)-based Editingmentioning
confidence: 99%
“…For example, the CRISPR–Cas system allows programmable control at multiple gene targets, using a catalytically inactive Cas9 (dCas9), a single guide RNA (sgRNA) to target DNA, and an associated effector protein to regulate transcription . Furthermore, chemically inducible systems that control the assembly, stability, or activity of the CRISPR–Cas complex can be used to regulate the timing of gene expression …”
Section: Figurementioning
confidence: 99%
“…This base‐editing method will have tremendous advantages because DNA cleavage can result in cytotoxicity. Besides, controlled activation of enzymes for genome or epigenome editing by stimulation with small organic molecules or irradiation by light have shown that enzymes can be switched on/off at will . Further understanding of epigenetic mechanisms is required for specific epigenome regulation; the study of relationships between modification of histone proteins and DNA modification .…”
Section: Other Genome Editing Technologies and Future Directionsmentioning
confidence: 99%